Effect of an exercise-based cardiac rehabilitation program on quality of life of patients with chronic Chagas cardiomyopathy: results from the PEACH randomized clinical trial - Marcelo Carvalho Vieira; Fernanda de Souza Nogueira Sardinha Mendes; Paula Simplício da Silva; Gilberto Marcelo Sperandio da Silva; Flavia Mazzoli-Rocha; Andrea Silvestre de Sousa; Roberto Magalhães Saraiva; Marcelo Teixeira de Holanda; Daniel Arthur Barata Kasal; Henrique Silveira Costa; Juliana Pereira Borges; Michel Silva Reis; et al. (Scientific Reports, 2024)
Abstract To investigate the effect of an exercise-based cardiac rehabilitation program on the quality of life (QoL) of patients with chronic Chagas cardiomyopathy (CCC). PEACH study was a single-center, superiority randomized clinical trial of exercise training versus no exercise (control). The sample comprised Chagas disease patients with CCC, left ventricular ejection fraction < 45%, without or with HF symptoms (CCC stages B2 or C, respectively). QoL was assessed at baseline, after three months, and at the end of six months of follow-up using the SF-36 questionnaire. Patients randomized for the exercise group (n = 15) performed exercise training (aerobic, strength and stretching exercises) for 60 min, three times a week, during six months. Patients in the control group (n = 15) were not provided with a formal exercise prescription. Both groups received identical nutritional and pharmaceutical counseling during the study. Longitudinal analysis of the effects of exercise training on QoL, considering the interaction term (group × time) to estimate the rate of changes between groups in the outcomes (represented as beta coefficient), was performed using linear mixed models. Models were fitted adjusting for each respective baseline QoL value. There were significant improvements in physical functioning (β =  + 10.7; p = 0.02), role limitations due to physical problems (β =  + 25.0; p = 0.01), and social functioning (β =  + 19.2; p < 0.01) scales during the first three months in the exercise compared to the control group. No significant differences were observed between groups after six months. Exercise-based cardiac rehabilitation provided short-term improvements in the physical and mental aspects of QoL of patients with CCC. Trial registration: ClinicalTrials.gov Identifier: NCT02517632; August 7, 2015.